Table of Content - -, (Arab Journal for Sciences and Research Publishing, 2025)
Table of Content:1. The image of the General Entertainment Authority among a sample of male and female students at King Abdulaziz UniversityMs. Rahaf Hmeed Alotaibi ,Prof. Fatima kobibi Bendenia2. Aesthetic Modernity and Its Dilemmas: Art between the Demand for Independence and the bet of Penetrating Public SpaceMr. Ahmed Chebli3. Social and Cultural Barriers to the Empowerment of Yemeni Women in Public Employment (An Analytical Field Study)Ms. Fatima Ali Abdullah Abbas4. The pragmatic dimension of pronunciation in The Maqamat of Badi’ Al-Zaman Al-Hamdhani- the Maqamat Al-Harziyya as an exampleMs. Alia Ali Saeed Alketbi, Dr. Muhammad Hilmi bin Abdullah bin Jaafar5. The role of the media in spreading digital awareness among members of society in the Kingdom of Saudi ArabiaEng. Faris Omar Batawi, Ms. Doaa Hassan Toweirqie
Keywords: Arab Journal of Sciences & Research Publishing